Satisfaction Determinant and The Implication of Employee Retention - Mar'atul Khosi'ah; Emiliana Sri Pudjiarti; Sulistyani Sutarlan (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2023)
This study aims to examine the effect of the work environment and the involvement of temporary employees on employee retention and to examine the effect of the mediating variable on job satisfaction. The object of research is DINDAGKOP UKM in Demak Regency. The method of collecting data is through a survey on 119 honorary employees of DINDAGKOP UKM. Sampling using nonprobability sampling. The results of the study explain that the work environment and employee engagement do not affect employee retention, but the work environment and employee engagement have a positive and significant effect on job satisfaction. Job satisfaction is a mediating variable of the relationship between the work environment and employee engagement on employee retention. This research implies that the human capital unit must have an employee retention plan, not only focusing on personnel administration by ignoring employee retention because it will have a bad impact on the organization. Because employee turnover increases, it will have an impact on work discomfort and can reduce employee work performance.